2021
DOI: 10.1002/adhm.202100402
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesized Selenium Nanoparticles‐Decorated Bacterial Cellulose/Gelatin Hydrogel with Enhanced Antibacterial, Antioxidant, and Anti‐Inflammatory Capabilities for Facilitating Skin Wound Healing

Abstract: Bacterial-associated wound infection and antibiotic resistance have posed a major burden on patients and health care systems. Thus, developing a novel multifunctional antibiotic-free wound dressing that cannot only effectively prevent wound infection, but also facilitate wound healing is urgently desired. Herein, a series of multifunctional nanocomposite hydrogels with remarkable antibacterial, antioxidant, and anti-inflammatory capabilities, based on bacterial cellulose (BC), gelatin (Gel), and selenium nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(110 citation statements)
references
References 54 publications
(66 reference statements)
1
101
0
8
Order By: Relevance
“…Innovatec and Axcelon Dermacare Inc., are two other firms that have announced their BNC vascular graft-based device tubing ( Czaja et al, 2007 ; Portela et al, 2019 ). Furthermore, Mao, Lin et al devised hydrogel by in-situ synthesis of selenium nanoparticles coated with BC/gelatin which represents increased antibacterial, antioxidant, and anti-inflammatory properties to aid skin wound healing ( Mao et al, 2021 ). Figures 8 , 9 exhibit typical applications of BNC in biomedical field.…”
Section: Resultsmentioning
confidence: 99%
“…Innovatec and Axcelon Dermacare Inc., are two other firms that have announced their BNC vascular graft-based device tubing ( Czaja et al, 2007 ; Portela et al, 2019 ). Furthermore, Mao, Lin et al devised hydrogel by in-situ synthesis of selenium nanoparticles coated with BC/gelatin which represents increased antibacterial, antioxidant, and anti-inflammatory properties to aid skin wound healing ( Mao et al, 2021 ). Figures 8 , 9 exhibit typical applications of BNC in biomedical field.…”
Section: Resultsmentioning
confidence: 99%
“…These results further demonstrate that the BC/CMC/Gly/yeast composite film possesses antibacterial activity against both Gram-positive ( S. aureus ) and Gram-negative bacteria ( P. aeruginosa and E. coli ). Previous studies have reported that both pristine BC [ 26 ] and CMC [ 64 ] do not possess any antibacterial activities, and these only show antibacterial activity when composited with other bactericidal elements such as metal nanoparticles [ 75 , 76 ], antimicrobial peptides [ 77 ], and some polymers such as chitosan [ 78 ]. Similarly, Gly is only used as the carbon source by different microorganisms and does not demonstrate any antibacterial activity [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…4.1.5. Bacterial Cellulose Based Self-Healing Hydrogel for Wound Healing Bacterial cellulose is an excellent hydrogel system used for wound healing, drug delivery, and tissue engineering applications [107][108][109]. Khamrai et al developed a bioderived self-healing wound healing patch made of curcumin loaded onto gelatin and ionically modified bacterial cellulose composite.…”
Section: Nanoparticles In Self-healing Hydrogels For Wound Healingmentioning
confidence: 99%